It's The End of the World and I'm In My Bathing Suit - Reynolds, Justin A. (New York : Scholastic Press, 2022)
When the electricity goes out, twelve-year-old Eddie and his friends set out to investigate what is going on when they make the startling discovery that they are the only ones left in their neighborhood--and perhaps the only people left anywhere.
new j 2022 spring.
Ages 8-12.
Grades 4-6.
Keywords: African American children -- Juvenile fiction; Electric power failures -- Juvenile fiction; Disasters -- Juvenile fiction; Survival -- Juvenile fiction; Friendship -- Juvenile fiction; Electric power failures -- Fiction; Disasters -- Fiction; JUVENILE FICTION / Dystopian; JUVENILE FICTION / Social Themes / Friendship; Survival -- Fiction; Friendship -- Fiction; African Americans -- Fiction; Humorous fiction